IMPLEMENTASI DISIPLIN GURU SD DALAM MENTAATI PERATURAN PERUNDANGUNDANGAN TENTANG DISIPLIN PNS DI UPPK TAMAN DINDIKPORA KABUPATEN PEMALANG - Gunarto Gunarto; Iman Teguh (UNISSULA, 2015)
Elementary teachers are professional educators with the primary task of educating, teaching, guiding, directing, train, assess, and evaluate students. Implementation of Government Regulation No. 53 of 2010 on Discipline of Civil Servants and Pemalang decree No. 26 of 2012 on Days and Hours of Work PNS Pemalang regency government, which regulates the working hours of teachers pose problems for elementary school teachers. This research method using sociological juridical approach. The results mentioned: 1) Implementation discipline elementary school teacher for adhering to regulations concerning thediscipline of civil servants in UPPK Park is the implementation of Government Regulation No. 53 of 2010 on Discipline of civil servants, and the decree Pemalang Number 26 Year 2012 on Days and Hours of Work PNS District Government Pemalang. 2) The problems that arise are not all elementary school teachers to obey the rules of discipline of civil servants on working hours of civil servants, 3) solution the problems that arise include: a) Orientation on elementary school teachers on discipline regulations on working hours PNS PNS. b) Monitoring the implementation of discipline Elementary School Teacher of regulations more intensified civil servants workinghours. c) Provision of strict sanctions for elementary school teachers who violate the rules of discipline of civil servants in working hours of civil servants obey. d) The reset of the timingof the task of the teacher so the teacher can carry out all tasks without violating civil service disciplinary regulations on working hours of civil servants.